Multi-sectoral analysis of strategic groups in franchising: A study in Italy - José M. Ramírez-Hurtado; Bernardino Quattrociocchi (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2018)
Franchising is a commercial form which enables firms to successfully penetrate the market and expand in an environment of growing global competitiveness. This form of business is present in many different activities and sectors, having its own characteristics and structures and significant differences among firms. It is therefore important to identify possible homogeneous groups of franchisors which share the same business strategies. This work is centred on the system of franchises in Italy. The figures about the high number of franchisors and franchised establishments, the quantity of chains operating over many years and the high penetration in the different sectors mean that franchising in Italy has a high degree of competitiveness and maturity. All this, along with the scarcity of studies about strategic groups in franchising in Italy, justifies this study. Specifically, the objectives are: 1) to identify the possible existence of strategic groups in Italy's franchising system; 2) to carry out a multisectoral analysis of strategic groups to determine whether the same strategic groups exist in the different franchising sectors; and 3) to characterise the different strategic groups and show their most significant variables. The results indicate that the most numerous strategic group is made up of chains which fully trust the domestic market, so the majority have not undertaken a strategy of internationalisation. On the other hand, the least numerous strategic group is composed of chains which have grown rapidly. This reaffirms the degree of saturation of the franchising market in Italy, as there is a great number of brands but few franchised establishments. The results attained in this work allow an understanding of the keys to the success of franchises in the Italian market for the franchisors to be able to maintain their position or, contrariwise, make changes and reposition themselves.
Keywords: M31; L29; 330; strategic group; franchising; operational variables; principal component analysis; Italy